A Probabilistic Model of Social Choice: Comment - Fishburn, Peter C. (Review of Economic Studies, 1975)
Journal Article A Probabilistic Model of Social Choice: Comment Get access Peter C. Fishburn Peter C. Fishburn The Pennsylvania State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 2, April 1975, Pages 297–301, https://doi.org/10.2307/2296538 Published: 01 April 1975